TRAINING ON ELECTRONIC RECORDS MANAGEMENT SYSTEMS TO IMPROVE OTKP STUDENTS’ COMPETENCIES AT SMK NEGERI 7 MEDAN - Rahdini Rizki Saragih; Fivi Rahmatus Sofiyah; Naomi Karina Hutagalung (RADJA PUBLIKA, 2026)
This community service program purpose to enhance the competencies of vocational high school students through training on electronic records management systems to reduce the competency gap between vocational education graduates and the demands of the digital workplace. The target participants were students of the Office Automation and Governance Program at SMK Negeri 7 Medan. A preliminary situation analysis revealed that students faced challenges in understanding electronic records management concepts, had limited experience in managing digital archives, and lacked readiness to utilize modern administrative technologies, including computer-based and cloud-storage systems. The program was implemented through workshops on electronic records management, hands-on practice in digital archive management, application-based document filing simulations, and mentoring and evaluation activities. These methods were designed to provide practical learning experiences that enabled students to apply electronic records management procedures in accordance with modern office administration standards. SMK Negeri 7 Medan supported the program by providing facilities and promoting the sustainability of digital-based learning practices. The expected outcomes included improved student knowledge and practical skills in electronic records management, documentation of activities through photographs and videos, and the publication of a journal article. This program is expected to strengthen students’ digital competencies and improve their readiness to compete in the technology-driven workplace.